2010
DOI: 10.3111/13696998.2010.499813
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of tiotropium for chronic obstructive pulmonary disease: a systematic review of the evidence

Abstract: The main conclusions of the economic evaluations derived from clinical trial data at the time of product approval and from later observational data reflecting clinical use are similar: use of tiotropium monotherapy is associated with lower hospital and other non-drug costs and better health outcomes and is either cost saving or cost effective compared with other maintenance monotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Tiotropium provides better health outcomes than standard monotherapies for a cost that represents value for money [54]. Often, it produces cost savings and is therefore the dominant product [55].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…Tiotropium provides better health outcomes than standard monotherapies for a cost that represents value for money [54]. Often, it produces cost savings and is therefore the dominant product [55].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…4 Several published economic evaluations have shown that treatment with tiotropium leads to lower hospital costs and better health outcomes compared to monotherapies, resulting in cost-savings or cost-effectiveness favouring tiotropium. 7 In a recent systematic review, Mauskopf and colleagues identified five model based economic evaluations assessing the cost-effectiveness of tiotropium over 1year (N Z 3) and 5-year time horizons (N Z 2). 7 All of these studies modelled effect based on data from short-term clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…7 In a recent systematic review, Mauskopf and colleagues identified five model based economic evaluations assessing the cost-effectiveness of tiotropium over 1year (N Z 3) and 5-year time horizons (N Z 2). 7 All of these studies modelled effect based on data from short-term clinical trials. The 5-year models relied on the extrapolation of data beyond the then available trial treatment periods.…”
Section: Introductionmentioning
confidence: 99%
“…It could also have been that tiotropium in usual practice had little or no advantage over ipratropium in improving those measures. A systematic review of tiotropium cost-effectiveness concluded that tiotropium is either cost-saving or cost-effective compared to other maintenance monotherapies [24]. However, the review, which used mostly data from randomized trials, also found that total costs were lower with tiotropium in some but not all studies included in the analysis.…”
Section: Discussionmentioning
confidence: 89%